Rancang Bangun Portable Weather Station Berbasis Jaringan Sensor Nirkabel Menggunakan Koneksi VPN - Aldiram Pritalaksa; Muhammad Abdul Hadi; Muhammad Hidayattullah (Universitas Indraprasta PGRI Jakarta, 2019)
In Law No. 31 of 2009 concerning Meteorology, Climatology and Geophysics and Government Regulation No. 11 of 2016 concerning Meteorology, Climatology and Geophysics Services related to BMKG, government institutions, and aid provider institutions Better as routine or as early. Problems related to the challenges in providing quality services and service information about weather and related interests do not only occur in Indonesia, but also in other countries. This is due to limited resources needed by this country. This problem was then carried out by BMKG to find alternative solutions to improve service information and complexity. The alternative that can be done is by partnering with the private sector or community. This study answers the questions and needs stated above, namely by making a prototype. Portable devices for easy use BMKG can use easy and simple. Thus many people and the private sector can use the prototype and related information and can be provided easily and simply. The technique used in taking measurement parameters is not expensive and the climate uses sensors installed in the NodeMCU v3 microcontroller. 5 weather and climate measurement parameters are used, namely air temperature & humidity, air pressure, wind speed, sunlight intensity and rainfall. The use of solar panels and dry batteries functioned as a power supply from this prototype design. The measurement results from the sensor by the microcontroller, then sent every 1 minute to the Raspberry Pi available in the operating room via a LAN connection and then recorded by history data. Then the data from the Raspberry is sent to the Web DB & Server Server every 1 hour via a VPN internet connection. Users can use weather information from the measurement results by accessing the Web Server via a VPN internet connection using a username & password that was previously registered. Keywords: Portable, Sensor, Microcontroller, Wireless, VPN